2018
DOI: 10.3390/catal8020067
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Wet Oxidation of Pharmaceutical Sludge by Molecular Sieve Loaded with Cu/Ce

Abstract: Abstract:In the present study, the catalytic wet oxidation of pharmaceutical sludge by molecular sieve loaded with Cu/Ce as catalyst was investigated. Experiments were performed in an experimental batch reactor. Reaction parameters including catalyst dose, temperature, time, and oxygen pressure were discussed. The results showed that the catalysts prepared by co-precipitating method have good catalytic performance. Under optimum conditions, the highest volatile suspended solids (VSS) removal rate approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…In our previous study, we also investigated several catalysts for the wet oxidation of pharmaceutical sludge and wastewater. We found that the prepared Cu–Ce/γ-Al 2 O 3 catalyst has good performance 28 30 . The catalyst was synthesized by a typical wet impregnation procedure.…”
Section: Resultsmentioning
confidence: 83%
“…In our previous study, we also investigated several catalysts for the wet oxidation of pharmaceutical sludge and wastewater. We found that the prepared Cu–Ce/γ-Al 2 O 3 catalyst has good performance 28 30 . The catalyst was synthesized by a typical wet impregnation procedure.…”
Section: Resultsmentioning
confidence: 83%
“…However, the wet oxidation method cannot produce uniform structures and thus not suitable for the fabrication of good quality nanogap structures. A typical example of a schematic diagram of the wet oxidation process is shown in Figure 10 124 …”
Section: Methods For Fabrication Of Nanogap Structuresmentioning
confidence: 99%
“…The wet oxidation process is a process where a thin oxidation layer can be introduced to semiconductor surfaces such as silicon and normally water vapor is introduced into the heated oxidation tube. 124 In most semiconductor industries, this process grows the oxide layer where the growth rate of oxide is 1000-1200 Ǻ/h. It is simple and easy to do especially when dealing with silicon and siliconrelated materials.…”
Section: Wet Oxidationmentioning
confidence: 99%
“…Previously, we have reported the addition of second metal would significantly increase the selectivity of the catalyst toward the target product but the low C 2 H 2 conversion, such as SrCl 2 and ZnCl 2 [22,23] ; however, the reaction mechanism and deactivation principle have not been mentioned. Combined with other related reports, [24][25][26] we start with magnesium metal additives to reveal the role of the second metal in the dimerization of acetylene and the possible reaction mechanism. In the Nieuwland catalytic system, the addition of magnesium as a second metal will significantly increase the acetylene conversion rate and the selectivity toward vinyl acetylene.…”
Section: Introductionmentioning
confidence: 99%